Combined maxillary sinus floor elevation and endonasal endoscopic sinus surgery for coexisting inflammatory sinonasal pathologies: a one‐stage double‐team procedure. Issue 12 (16th October 2014) - Abu‐Ghanem, Sara; Kleinman, Shlomi; Horowitz, Gilad; Balaban, Sagi; Reiser, Vadim; Koren, Ilan
Abstract: Objectives: To report our experience with combined one‐stage double‐team maxillary sinus floor elevation (SFE) and endonasal endoscopic sinus surgery (ESS) procedure for concomitant inflammatory sinonasal pathologies. Material and methods: Clinical records of all patients that underwent maxillary SFE in conjunction with endonasal ESS for the treatment of inflammatory sinonasal pathologies between 2011 and 2013 were retrospectively reviewed. All included patients had a sinonasal‐related pathology that was first suggested by the referring physician and was later confirmed clinically and radiographically by our combined team comprised of otorhinolaryngologist and maxillofacial surgeons. Results: Fifteen combined SFE+ESS surgeries were performed using either xenograft–allograft mixture or autograft–xenograft–allograft mixture. The study group included seven males and eight females, whose median age was 55 years (range, 45–78 years). Seven patients underwent a unilateral SFE, and eight patients underwent bilateral SFEs. During the same session, four patients also underwent septoplasty for deviated nasal septum, five patients underwent bilateral maxillary antrostomy, 10 patients underwent unilateral maxillary antrostomy, and six patients underwent maxillary sinus cyst resection. Seven combined procedures were performed under active infection. There were no intra‐operative complications, and all SFE+ESS combined procedures were successful. Three patients required extended postoperative antibiotic treatment for persistent sinusitis. One patient reported infraorbital hypoesthesia. Conclusions: We first report the promising outcomes of the double‐team one‐stage SFE+ESS procedure performed by a combined team of otorhinolaryngologist and maxillofacial surgeons, including on patients presenting with an infection of the sinuses at the time of surgery.